The Impact of Tax Audits on the Quality of Financial Reporting of Corporate Taxpayers in Indonesia - Irma Herliza Rizki; Mela Novita Rizki (Outline Publisher, 2024)
This study aims to analyze the effect of tax audits on the quality of financial reporting of corporate taxpayers in Indonesia. Tax audits are a strategic instrument used by tax authorities to improve taxpayer compliance, especially in terms of preparing financial reports. In the digital era, tax audits have been supported by information technology that facilitates data monitoring and validation. This study uses a quantitative approach with a survey method on corporate taxpayers in various industrial sectors. Data were analyzed using a linear regression model to measure the relationship between the intensity of tax audits and the quality of financial reporting. The results of the study indicate that tax audits have a significant positive effect on the quality of financial reporting. Corporate taxpayers who frequently undergo audits tend to present more accurate financial reports and in accordance with accounting standards, due to the pressure to avoid potential sanctions. In addition, the use of digital technology in tax audits strengthens this relationship by increasing the transparency and efficiency of the audit process. However, this study also identifies challenges, such as the limited number of tax auditors and the complexity of financial reports, which can hinder the effectiveness of audits.